A Non-Anesthetized Mouse Model for Recording Sensory Urinary Bladder Activity - Zvara, Peter; Wright, Andrew J.; Roach, Kristopher; Ursiny, Michal; Shapiro, Bennett; Dagrosa, Lawrence M.; Nelson, Mark T.; Heppner, Thomas J. (Frontiers in Neurology, 2010)
The goal of this study was to develop an in vivo awake mouse model for extracellular bladder sensory nerve recording. A bipolar 125-µm silver electrode was positioned under a single postganglionic bladder nerve. Efferent nerve signals were eliminated by tying off the postganglionic bladder nerve between the major pelvic ganglion and the recording electrode. Sensory nerve activity was measured in the conscious animals 48 hours after surgery during continuous intravesical infusion of 0.9% saline/0.5% acetic acid followed by 0.5% acetic acid with capsazepine (10 µM) at a rate of 0.75 ml/h. Continuous infusion of 0.9% NaCl led to a gradual increase in the frequency of sensory nerve firing that peaked upon reaching threshold pressure. Non-micturition contractions were observed in some animals during filling and other animals exhibited only minimal pressure fluctuations; both types of events were associated with a rise in sensory nerve activity. Intravesical infusion of 0.5% acetic acid reduced the intermicturition interval. This was associated with a 2.1-fold increase in bladder pressure during filling and a 2-fold increase at both threshold and micturition pressures. Concurrent with these changes, sensory activity increased 2.8-fold during filling and 2.4-fold at threshold pressure. Subsequent intravesical infusion of capsazepine in 0.5% acetic acid reduced filling and threshold pressures by 21% and 31.2%, respectively, and produced corresponding decreases of 36% and 23.4% in sensory nerve activity. The current study shows that multi-fiber sensory nerve recordings can be reproducibly obtained from conscious mice.